Growth Concerns in Coffin–Lowry Syndrome: A Case Report and Literature Review - Lv, Ying; Zhu, Liuyan; Zheng, Jing; Wu, Dingwen; Shao, Jie (Frontiers in Pediatrics, 2019)
Mutation of RPS6KA3 can induce Coffin–Lowry syndrome, an X-linked syndrome. The case we reported here manifests its signature characteristic of short stature, facial dysmorphism, development retardation, hearing defect. The mutation of RPS6KA3 we detected by NGS analysis is c.2185 C>T. The short stature is a noteworthy problem we discuss here to improve his growth and development. The efficacy and safety of application of growth hormone analogues on patients of CLS are not confirmed and need to be especially careful.